Reading French in Early Nineteenth-Century New York: The New York Society Library as Agent of Cultural Exchange - Furlong, Jennifer (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2019)
The circulation records of the New York Society Library contextualize late eighteenth-century New Yorkers’ engagement with French-language books and authors. Founded in 1754, the Society Library holds extant circulation records that date from 1789–1792 and 1799–1806. These records reveal what eighteenth-century readers were checking out of the library and presumably reading. The paper analyzes both quantitative and qualitative data related to readers’ borrowing practices and examines which French works were most often borrowed. This, in turn, allows us to speculate on what might have been the appeal of these works in the complex cultural environment of the early American republic. Finally, this paper seeks to understand why Anglophone readers chose to read in French, particularly when English-language titles were available, what they gained from this practice, and how these works supported the intellectual aspirations of a new nation.